Study of models of e-cigarette use among adolescents: motivation, perception, and influence of marketing - Skipalsky, A.P.; Khomenko, I.M.; Kupyra, D.I. (Environment & Health, 2025)
This study explores the use of tobacco and nicotine products among adolescents in Ukraine, focusing on electronic cigarettes (e-cigarettes) as the most commonly used product. It examines motivations, risk perceptions, marketing influences, and awareness of health harms and cessation support.Key motivators include curiosity, peer pressure, imitation of adults or peers, stress relief, and appealing flavors. Many respondents perceive e-cigarettes as less harmful than conventional cigarettes, creating a false sense of safety. While some awareness of health risks exists, knowledge of cessation services remains low. The presence of e-cigarette marketing, especially in digital spaces, contributes to the romanticization of use.Findings highlight the need for a comprehensive response: stricter legal restrictions, tighter advertising controls, limited youth access, and stronger educational efforts. These results can inform more targeted prevention and control strategies for youth nicotine use.